Meme Marketing: Generation Z Consumer Behavior on Social Media - Arie Bowo, Ferdian; Anisah, Anisah; Marthalia, Lia (Jurnal Indonesia Sosial Sains, 2024)
This study investigates the phenomenon of "Meme Marketing" and its impact on the consumer behavior of Generation Z on social media. The research focuses on the characteristics, classification, coherence levels, and format evolution of memes, as well as their role in marketing strategies. Meme characteristics, such as fidelity, fecundity, longevity, and additional elements like relevance, ease of replication, uniqueness, and humor, are identified as key influencers on meme dissemination. Meme classification involves four types proposed by Knobel and Lankshear, along with considerations of genre, format, and media, providing an overview of meme diversity. The transformation of meme formats, from single images to GIF videos, reflects adaptation to trends and social media technology. The role of memes in marketing strategies goes beyond brand awareness, becoming a source of innovation in the cultural industry. Humor, as a key element, plays a crucial role in attracting attention and creating appeal for consumers. Meme virality factors, such as relevance, iconicity, humor, and format, require effective embedding and distribution strategies. In the context of Generation Z consumer behavior, memes provide satisfaction in entertainment, social interaction, and information. Media factors, including embedding and distribution strategies, are crucial for the successful dissemination of memes and consumer engagement. Applying marketing theory frameworks, this research offers both theoretical and practical implications for the development of effective marketing strategies in the digital era